Strategic Business Alliances : concepts, laws, practices & precedents - Igwe, J. U. K. (Abuja, Nigeria, 2008)
The book examines the importance of tax incentives to companies and industries, particularly in making decisions on where to invest.
volume 3. Joint ventures, franchising, partnership, mergers, takeovers & acquisitions
Loans